Literacy, sexuality, pedagogy: theory and practice for composition studies - Alexander, Jonathan, author; Utah State University Press, publisher (Colorado State University. Libraries, 2008)
In this book, Jonathan Alexander argues for the development of students' sexual literacy. Such a literacy is not just concerned with developing fluency in sexuality as a "hot" topic, but with understanding the intimate interconnectedness of sexuality and literacy in Western culture. Alexander unpacks what he sees as a crucial dimension of literacy: the fundamental ways in which sexuality has become a key component of contemporary literate practice, of the stories we tell about ourselves, our communities, and our political investments.--Book jacket.
Introduction: Toward sexual literacy -- Sites of theory and writing: Discursive sexualities: bridging sexuality and literacy studies -- Beyond textbook sexuality: students reading, students writing -- Sites of pedagogy: Queer theory for straight students sex and identity -- Transgender rhetorics sex and gender -- Straight talk about marriage: sex and politics -- Sites of resistance: Susie Bright in the Comp class: confronting resistances.
Keywords: Authorship -- Study and teaching (Higher) -- Social aspects; English language -- Rhetoric -- Study and teaching -- Social aspects; Gender identity; Sex